Penumbuhkembangan Motivasi Guru Madrasah Tsanawiyah Mambaul Ulum Perdana dalam Peningkatan Kualitas Pendidikan - Syafii, Muhammad Lukman; Kusnawan, Wawan; Syukroni, Azid (Universitas Muhammadiyah Yogyakarta, 2020)
MTs Mambaul Ulum that has been founded in academic year of 2019/ 2020 should be responsive and adaptive towards the development dynamics of Education field. The use of information technology in Education field has to be anticipated and prepared by teachers, students, and educational workers. The key of success in accommodating the advancement of the era is determined by strong motivation from all components especially teachers. Therefore, the goal of the service program is directed to grow the motivation of teachers in the effort to improve Education quality in Mts Mambaul Ulum. The program implementation was conducted in stages, namely problem identification, program socialization, motivation seminar for students, teachers, parents/ guardian, leaders of the Foundation, and school environment. The result of the social service activity is the growing of strong motivation in all components, and stakeholders can build the relation harmonization among all components towards quality Education in the digital era.